Dobrostan psychiczny jako predyktor szczęścia według teorii psychologicznych - Grzanka, Anna (Kultura-Społeczeństwo-Edukacja, 2024)
According to the World Health Organization data in 2019, 301 million people were affected by anxiety disorders, and 280 million were grappling with various forms of depression. In the same year, almost a billion individuals, including 14 percent of teenagers, experienced issues related to mental well-being. The above statistics do not inspire optimism and clearly indicate a deteriorating global mental health situation. In contrast to mental health crises stands psychological well-being, with one of its main determinants being mental well-being. The sense of well-being or its absence applies to every individual, making it an intriguing subject. Despite geographical, cultural, socio-economic, and even genetic differences, everyone aspires to mental well-being. Delving into the concept of well-being is a crucial step in the journey towards personal happiness and satisfaction. Through a deeper understanding of what influences our individual sense of well-being, we can better tailor our actions and life goals to our own needs and values. The article presents various psychological concepts related to well-being, including positive psychology and health psychology, personality theories, Janusz Czapiński’s onion model of happiness, Aaron Antonovski’s salutogenic model, perspectives from gerontology, with a special focus on Lars Tornstam’s theory of gerotranscendence, and considerations from the standpoint of workplace well-being.